2019
DOI: 10.1111/cge.13616
|View full text |Cite
|
Sign up to set email alerts
|

Genetic spectrum and clinical profiles in a southeast Chinese cohort of Charcot‐Marie‐Tooth disease

Abstract: Charcot‐Marie‐Tooth (CMT) disease is a heterogeneous group of inherited sensorimotor neuropathies. To clarify the genetic spectrum and clinical profiles in Chinese CMT patients, we enrolled 150 unrelated CMT patients from southeast China. We performed multiplex ligation‐dependent probe amplification (MLPA) testing in all patients and next‐generation sequencing (NGS) among those patients without PMP22 rearrangements. We identified PMP22 duplications in 40 patients and deletions in 12 patients. In addition, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 42 publications
(111 reference statements)
2
21
2
Order By: Relevance
“…Besides the three families carrying variants in GDAP1 in this study, we have previously reported three GDAP1 variants (p.W31*, p.Q38*, p.V215I) in two patients 22 . The locations of seven variants from our studies and 10 variants from other Chinese studies in the structure of GDAP1 protein are shown in Figure 1C.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Besides the three families carrying variants in GDAP1 in this study, we have previously reported three GDAP1 variants (p.W31*, p.Q38*, p.V215I) in two patients 22 . The locations of seven variants from our studies and 10 variants from other Chinese studies in the structure of GDAP1 protein are shown in Figure 1C.…”
Section: Resultssupporting
confidence: 58%
“…Herein, we focus on the three novel variants (p.L26R, p.S169fs, c.694 + 1G>A) and one known variant (p.R120W) in GDAP1 . Taking three variants previously reported in two patients into consideration, 22 we can summarize a frequency distribution of 2.78% (5/180) in GDAP1 . Previous studies in the Chinese population showed a similar frequency 4,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides the three families carrying variants in GDAP1 in this study, we have previously reported three GDAP1 variants (p.W31X, p.Q38X, p.V215I) in 2 patients (Chen et al, 2019). The location of 7 variants from our studies and 10 variants from other Chinese studies in the structure of GDAP1 protein are shown in Fig.…”
Section: Genetic Analysissupporting
confidence: 56%
“…Herein, we focus on the three novel variants (p.L26R, p.S169fs, c.694+1G>A) and one known variant (p.R120W) inGDAP1 . Taking 3 variants previously reported in 2 patients into consideration (Chen et al, 2019), we can summarize a frequency distribution of 2.78% (5/180) in GDAP1 . Previous studies in the Chinese population showed the similar frequency (Fu et al, 2017;Pakhrin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the discovery of many disease-causing genes in recent years, the genetic cause of ARCAs remains elusive in more than 50% of affected individuals [8,9]. The advent of whole-exome sequencing (WES) technology not only has enabled the e cient diagnosis with single-nucleotide variants (SNVs) and small indels [10], but also the new WES-based method, such as Exome Depth, has successfully detected structural variation (SV) like copy number variations (CNVs) in many hereditary diseases [11]. Moreover, owing to the low incidence, there are few studies reported the rare genetic or clinical characteristic of ARCA patients in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%